Strategic foundations for managing the competitiveness of construction enterprises in the paradigm of sustainable socio-economic development - ZGALAT-LОZYNSKA Liubov; DMYTRENKO, Hennadii; HOLOVACH, Nataliia (Ways to Improve Construction Efficiency, 2025)
The article is devoted to the theoretical and methodological substantiation of approaches to managing the market advantages of construction enterprises within the paradigm of sustainable socio-economic development. The relevance of the study is determined by the fact that, under conditions of wartime instability, post-war recovery, resource constraints, digital transformation, and increasing environmental requirements, traditional models of ensuring market resilience are losing their effectiveness. The purpose of the article is to substantiate theoretical provisions and to develop an analytical toolkit for assessing the competitive advantages of construction businesses based on the integration of economic, social, and environmental components, taking into account the decisive role of human capital. It is proposed to consider the market resilience of an enterprise as an integral ability to maintain its positions and form long-term advantages through the alignment of economic performance, social responsibility, and environmental balance in accordance with the logic of achieving the Sustainable Development Goals. A human-centered approach is substantiated, according to which professional competencies, innovative activity, managerial flexibility, and the quality of human resources determine the ability to create a unique product, improve quality, rationalize costs, and generate additional value for consumers. The provisions of the quadra of market success factors are further developed, and its innovation- and human-centered nature is revealed. An expert-utility approach to assessment is proposed, combining the determination of the significance of criteria and the level of satisfaction with them, while also taking into account the balance of the economic, social, and environmental blocks. The testing of the methodology on the example of two enterprises in Vinnytsia region showed that higher economic performance does not guarantee a better overall result if it is not accompanied by social resilience, adequate staffing, reputational reliability, and environmental responsibility. The practical significance of the obtained results lies in the possibility of using the proposed approach for strategic management, monitoring, and substantiation of decisions aimed at strengthening the market positions of construction enterprises.